Evaluasi Hasil Uji Tarik H-Beam Bj 41 Mengacu pada SNI 2610:2011 untuk Aplikasi Spreader Bar di Industri Migas - Dipta Ario Wibowo; M. Roni Hajianto; Hafid Suharyadi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study discusses the evaluation of the tensile test results of H-Beam BJ 41 steel to assess its conformity with the specifications stated in SNI 2610:2011 for H-shaped structural steel of the Bj PHC 400 class. The test was conducted on two H-Beam specimens with a thickness of less than 16 mm to determine the main mechanical parameters, namely yield strength, ultimate tensile strength, and elongation. Tensile testing was carried out using a Universal Testing Machine (UTM) Gotech GT-7001-LS 50, resulting in average values of yield strength at 314.5 N/mm², ultimate tensile strength at 454 N/mm², and elongation at 41.5 %, with relatively small deviations between specimens. These results fully meet and even exceed the minimum requirements specified in SNI 2610:2011, which stipulate yield strength ≥ 245 N/mm², ultimate tensile strength of 400–510 N/mm², and elongation ≥ 17 %. The findings indicate that H-Beam BJ 41 possesses excellent strength and ductility with consistent material quality, making it suitable for use as a spreader bar material in heavy equipment lifting applications within the oil and gas industry, thereby supporting safety and structural reliability during lifting operations.